Building Customer Trust: An Empirical Study in Marketplace - Riwu, Yonas Ferdinand; Natonis, Sari Angriany; Arthana, I Komang; Anabuni, Anderias U. T.; Aman, Dominikus K.T (SAFE-Network, 2024)
This study aims to analyze how online customer trust is affected by online customer ratings and online customer reviews on the Tokopedia marketplace. This study used quantitative data and was analyzed with the help of SEM-Partial Least Squares (PLS). Data in this study as many as 96 respondents were obtained through online questionnaires with purposive sampling techniques. Results show that online customer reviews have an influence and significance on customer trust, this shows that others have had experience with the product or service. When potential customers see positive reviews from fellow customers, it validates the credibility and quality of the offer, thus building trust. Honest reviews from real customers carry more weight than promotional content from brands. Customers tend to trust their colleagues' opinions more than marketing messages because they perceive them as untendentious and reliable. When individuals feel associated with positive experiences shared by others, they feel more emotionally connected to the brand, which reinforces trust and drives purchase decisions. Then online customer rating has a significant effect on customer trust, it shows that when a product or service gets a high rating from a large number of customers, it signals to potential customers that the item is considered good by those who have used it before. People tend to believe in the majority. If most customers give a high rating to a product or service, potential buyers will tend to go with the flow and also have high trust in the item Customer ratings give a perception of the credibility of a brand or company. When a brand has consistently high rankings, it shows that the brand is considered reliable by customers, which in turn builds trust.